Deep learning approaches for Bengali cyberbullying cetection on social media: a comparative study of BiLSTM, BiGRU and BERT models - Fahim, Kaji Mehedi Hasan; Nyla, Nasita; Saha, Priti; Akter, Mst. Shamima; Shourav, Musfiqur Rahman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.